A new transient phenomenon caused by active current dynamics of grid-following converters during severe grid faults - Wu, Chao; Huang, Zhanqi; Wang, Yong; Blaabjerg, Frede (Frontiers in Energy Research, 2024)
Existing transient stability analysis of grid-following (GFL) converters mainly focuses on the dynamics of the phase-locked loop (PLL), while current loop dynamics are usually neglected due to their faster response than PLL. However, this article reveals that active current may not be able to track its reference quickly during severe grid faults even with high current loop bandwidth, which leads to a non-negligible impact on the transient stability of GFL converters. Furthermore, this article discusses the intrinsic mechanism of why active current cannot track its reference quickly during severe grid faults and establishes a refined third-order transient synchronization model that offers a more accurate assessment of transient stability during severe grid faults than the conventional second-order model.